2011
DOI: 10.4103/0019-5359.103963
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study to assess quality of life and prescription pattern in osteoarthritis patients at tertiary health centre in Mumbai

Abstract: Osteoarthritis has a significant impact on quality of life, only partly ameliorated by anti-arthritic drugs, as assessed by the WOMAC scale in this study population. Further, a study with larger sample size is needed to further support our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
4
3
0
Order By: Relevance
“…8 The mean age of osteoarthritis affected population in our study was 56.46+/-7.4 years. The same age group is also commonly affected by osteoarthritis according to a study done by Kulkerni et al 9 Among various sites involved in osteoarthritis, knee joint (87.33%) was most commonly affected site which is in accordance with other such studies including Jadhav et al 7 and Ullal et al 6 Average number of drugs per prescription is an integral determinant prescription audit. 10 In our study, the average number of drugs prescribed per prescription was 2.62+/-0.46.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…8 The mean age of osteoarthritis affected population in our study was 56.46+/-7.4 years. The same age group is also commonly affected by osteoarthritis according to a study done by Kulkerni et al 9 Among various sites involved in osteoarthritis, knee joint (87.33%) was most commonly affected site which is in accordance with other such studies including Jadhav et al 7 and Ullal et al 6 Average number of drugs per prescription is an integral determinant prescription audit. 10 In our study, the average number of drugs prescribed per prescription was 2.62+/-0.46.…”
Section: Discussionsupporting
confidence: 71%
“…This is in accordance with a study done by Ullal et al and Jadhav et al, in which 57.14% and 70.56% of affected patients were females respectively. 6,7 The importance of estrogen in prevention of osteoarthritis is explained in the study by Rowen et al with regards to the age distribution, a total of 176 patients (58.67%) belonged to the age group of 46-60years. 8 The mean age of osteoarthritis affected population in our study was 56.46+/-7.4 years.…”
Section: Discussionmentioning
confidence: 99%
“…In this present study, demographic distribution projected that OA was much more prevalent in females (60%) as compared to males (40%). Our study coincides with a study conducted by Ullal and Narendranath [8] and Jadhav et al [9] in which they documented 57.14% and 70.56% of patients diagnosed with OA were female patients [6,7]. Further a prospective and observational study conducted by Kulkarni et al among 84 patients also concluded that OA was more prevalent in females (63.1 %), and these results are parallel to our study in which 60% of females were duly affected by OA [10].…”
Section: Discussionsupporting
confidence: 93%
“…In the reviewed literature there is a significant correlation between the level of pain and 347 disability in OA patients. Pain created various limitations to varying degrees, not only in the 348 performance of professional duties, but also in daily activities and in the pursuing of personal 349 interests (Jadhav et al, 2001). Reis et al (2014) indicate that in women diagnosed with OA, 350 there is a significant relationship between the pain and the level of disability during performing 351 basic daily life activities, which is similar to our study result.…”
supporting
confidence: 83%